Variation rs2235503 C > A Within the Promoter of MSLN Affects Transcriptional Rate of Mesothelin and Plasmatic Levels of the Soluble Mesothelin-Related Peptide - Silvestri, Roberto; Pucci, Perla; De Santi, Chiara; Dell’Anno, Irene; Miglietta, Simona; Corrado, Alda; Nicolí, Vanessa; Marolda, Daniela; Cipollini, Monica; Pellegrino, Enrica; Evangelista, Monica; Bonotti, Alessandra; et al. (Frontiers in Genetics, 2020)
Soluble mesothelin-related peptide (SMRP) is a promising biomarker for malignant pleural mesothelioma (MPM), but several confounding factors can reduce SMRP-based tests accuracy. The identification of these confounders could improve the diagnostic performance of SMRP. In this study, we evaluated the sequence of 1000 base pairs encompassing the minimal promoter region of MSLN gene to identify expression quantitative trait loci (eQTL) that can affect SMRP. We assessed the association between four MSLN promoter variants and SMRP levels in a cohort of 72 MPM and 677 non-MPM subjects, and we carried out in vitro assays to investigate their functional role. Our results show that rs2235503 is an eQTL for MSLN associated with increased levels of SMRP in non-MPM subjects. Furthermore, we show that this polymorphic site affects the accuracy of SMRP, highlighting the importance of evaluating the individual’s genetic background and giving novel insights to refine SMRP specificity as a diagnostic biomarker.